Social Work Education and Health Equity in India: A Critical Review - Ngaopunii Trichao Thomas (Social Work and Society, 2024)
Considering the persistence of significant health inequities in India, exploring the interface between health equity and social work education is a critical research priority. This article attempts to present a systematic analysis of the present status of health equity and social work training in India, elaborating on healthcare discrepancies among various populations in India, examining reasons for elevated morbidity and mortality rates among marginalized communities, and approaches to social work education at present. Consequently, curriculum revision should be all-inclusive and focus on highlighting fairness in health provision as well as cultural competency with an emphasis on social justice. It also calls for a paradigm shift towards contextualized knowledge, critical pedagogy and community engagement to prioritize health equity by suggesting that future training should focus on a holistic approach to dealing with preventable illnesses emanating from these determinants. In conclusion, this article points out the significance of giving more attention towards health equity within Indian schools of social work while providing some directions for possible research lines.